2012
DOI: 10.1371/journal.pone.0041216
|View full text |Cite
|
Sign up to set email alerts
|

Neuronal Mechanisms of Voice Control Are Affected by Implicit Expectancy of Externally Triggered Perturbations in Auditory Feedback

Abstract: Accurate vocal production relies on several factors including sensory feedback and the ability to predict future challenges to the control processes. Repetitive patterns of perturbations in sensory feedback by themselves elicit implicit expectations in the vocal control system regarding the timing, quality and direction of perturbations. In the present study, the predictability of voice pitch-shifted auditory feedback was experimentally manipulated. A block of trials where all pitch-shift stimuli were upward, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

5
27
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 27 publications
(32 citation statements)
references
References 50 publications
5
27
0
Order By: Relevance
“…In addition, these findings suggest that exposure to repeated presentations of predictable stimuli results in the increased contribution of feedforward mechanisms during vocal motor control. This reasoning supports the framework for predictions by the internal forward model: learned predictions result in more accurate efference copies and, consequently, a decreased mismatch in sensory feedback (Chen et al, 2012; Korzyukov et al, 2012; Scheerer and Jones, 2014; Wang et al, 2014; Wolpert and Flanagan, 2001). …”
Section: Introductionsupporting
confidence: 74%
See 4 more Smart Citations
“…In addition, these findings suggest that exposure to repeated presentations of predictable stimuli results in the increased contribution of feedforward mechanisms during vocal motor control. This reasoning supports the framework for predictions by the internal forward model: learned predictions result in more accurate efference copies and, consequently, a decreased mismatch in sensory feedback (Chen et al, 2012; Korzyukov et al, 2012; Scheerer and Jones, 2014; Wang et al, 2014; Wolpert and Flanagan, 2001). …”
Section: Introductionsupporting
confidence: 74%
“…In the study by Scheerer & Jones (Scheerer and Jones, 2014), behavioral vocal responses to predictable and unpredictable pitch-shift stimulus magnitude were examined and they reported that the magnitude of vocal responses was significantly reduced for predictable vs. unpredictable stimuli. Behroozmand et al (Behroozmand et al, 2012) and Korzyukov et al (Korzyukov et al, 2012) examined the effect of pitch-shift stimulus direction predictability and found that the magnitude of opposing (compensatory) vocal responses to unpredictable stimulus direction was significantly larger than following responses (Behroozmand et al, 2012), and there was a significantly larger number of opposing responses for unpredictable vs. predictable stimulus direction (Korzyukov et al, 2012). Korzyukov et al (Korzyukov et al, 2012) and Scheerer & Jones (Scheerer and Jones, 2014) also reported that the amplitude of the N1 component of ERPs was significantly reduced for predictable vs. unpredictable stimulus direction and magnitude, respectively.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations